2018
DOI: 10.1136/archdischild-2017-314308
|View full text |Cite
|
Sign up to set email alerts
|

Volume targeting levels and work of breathing in infants with evolving or established bronchopulmonary dysplasia

Abstract: Only a tidal volume target of 7 mL/kg reduced the work of breathing below the baseline and may be more appropriate for infants with evolving or established BPD who remained ventilator dependent at or beyond 7 days of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 15 publications
(8 reference statements)
0
8
0
Order By: Relevance
“…The wide range of postnatal ages in our study population may have influenced our results, but advantages of PAV and NAVA over conventional ventilation have been demonstrated in infants with a variety of postnatal ages in previous studies. Targeted tidal volumes of between 5 and 7 mls/kg were used, as studies have shown chronically ventilated infants may require 7 mls/kg [29,30] and in the latter study (30) to reduce the work of breathing. It could be suggested that in babies with BPD 2hour epochs may not be sufficient to demonstrate changes in oxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…The wide range of postnatal ages in our study population may have influenced our results, but advantages of PAV and NAVA over conventional ventilation have been demonstrated in infants with a variety of postnatal ages in previous studies. Targeted tidal volumes of between 5 and 7 mls/kg were used, as studies have shown chronically ventilated infants may require 7 mls/kg [29,30] and in the latter study (30) to reduce the work of breathing. It could be suggested that in babies with BPD 2hour epochs may not be sufficient to demonstrate changes in oxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…For each breath, the beginning and end of inspiration was determined from the flow signal, in order to delineate the inspiratory work of breathing. The mean PTPdi of the first 20 artefact-free breaths in the last 5 min of each 20 min epoch of ventilation was calculated, as has previously been described [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…The increase in Vt requirement is greatest during the third week of life, which is presumed to be due to enlargement of the upper airways (acquired tracheomegaly) and an increase in alveolar dead space [80]. Interestingly, in infants with evolving or established BPD who remain ventilator-dependent at or beyond seven days of age, a Vt target of 7 mL/kg was found to reduce the work of breathing compared to smaller Vt (4-6 mL/kg) [81]. The application of VG was reported to be feasible even in extremely premature infants [82,83].…”
Section: Volume-targeted Ventilationmentioning
confidence: 99%